(untitled) (Hekima Review, 2020)
The story of Africa and African theology cannot be told without women. The chant ‘Wathinta abafazi, wathinta imbokodo’ was sung by women of all races in South Africa on 9th August 1956 during a protest march against apartheid pass laws. Similarly in the liberation struggles across Africa, African women sang and fought alongside their male counterparts for the liberation of the continent. Given this background it is not surprising that African women theologians rose up against patriarchy in religion and culture in 1989 to disrupt and create a new trajectory in theology that placed the lived experiences of women as the starting point for liberating theologies. Prior to women’s theologies were African theologies which emerged in contexts of the struggle for liberation from colonialism and apartheid but the priority of national liberation foregrounded other forms of oppression such as gender, class, ethnicity and sexual orientation. Hence the gender blindness of both liberation movements and African theologies. In response to this context African women theologians formed the The Circle of Concerned African Women Theologians as agents of their own liberation which they have always linked with the liberation of all. This article will celebrate the journey of women theologians past, present and future as they continue to break the silence on women’s lives and interrogate both religion and culture in the quest for theologies of liberation for women and the societies in which they are a part of.